Transformasi Pembelajaran PAI Melalui Pendekatan Deep Learning - Tisi Molina Putri; Shobah Shofariyani Iryanti (Institut Agama Islam Negeri Pontianak, 2026)
The main problem in Islamic Religious Education learning is the dominance of textual and memorization-oriented approaches that have not optimally developed students’ critical, reflective, and meaningful understanding of Islamic values. This study aims to examine the transformation of IRE learning through a deep learning approach as a strategy to enhance meaningful understanding and implementation of Islamic values. This study employed a qualitative approach using a Systematic Literature Review. Literature selection followed the PRISMA procedure through identification, screening, eligibility, and inclusion stages. The findings indicate that the deep learning approach transforms learning from mere knowledge transfer into a process emphasizing contextual understanding, reflective learning, and value internalization. The approach is implemented through inquiry learning, project-based learning, and reflective activities that encourage students to connect Islamic teachings with real-life experiences. Furthermore, deep learning supports the integration of cognitive, affective, and psychomotor dimensions in IRE learning, contributing to the development of critical thinking, religious awareness, and social responsibility. The study concludes that deep learning provides a transformative framework for creating meaningful, contextual, and value-oriented Islamic education.